Pengembangan Media Pembelajaran IPS Berbasis Website untuk Siswa Kelas VII Madrasah Tsanawiyah Negeri - Hamzah B Uno; Abd. Rahman K Ma'ruf (JTP - Jurnal Teknologi Pendidikan, 2016)
The aim of the research is IPS Learning Development Based on Website For Students Class VII MTs Negeri Gorontalo City. The aim of this study was to produce a IPS development of learning IPS based on web learning for students of class VII MTsN. Gorontalo. To know the effectiveness of based on web learning social studies for students of class VII MTsN. Gorontalo. The method used in this research is Research approach. and Development (R & D). Step in the research is through ADDIE models usage, in which the processes of development, namely: Analysis, Design, Development,implentation, and Evaluation. The results of this study are shown of: Assessment materials used by validation by 5 panelists were .0.80- 0.95 value range with the level of reliability is 0.80 so this shows that material is very fit for use, Assessment media used by validation by 5 panelists were range 0.65-0.95 value reliability level of 0.80 so this shows the media isreasonable to use.